Efficacy of white vinegar, 37% phosphoric acid and 10% hydrofluoric acid on the retrievability of bioceramic sealer: an in-vitro study - Tanjung, Dian Soraya; Daryono; Winata, Mellisa (Conservative Dentistry Journal, 2024)
Background: Root canal retreatment is performed when root canal treatment fails. One of the challenges in retreatment is the removal of root canal filling material. Bioceramic sealer is a new endodontic biomaterial that has many advantages. Nevertheless, the difficulty in retrieving bioceramic sealer in failed root canal treatment remains a controversy. Purpose: To investigate the efficacy of white vinegar, 37% phosphoric acid and 10% hydrofluoric acid in retrieving bioceramic sealer. Methods: Bioceramic sealer specimen was used as samples in this study consisting of 60 samples divided into four treatment groups. All groups were soaked in white vinegar, 37% phosphoric acid, 10% hydrofluoric acid and saline as negative control for 10 minutes. Microhardness testing was performed using Vickers Microhardness Tester, then all data were statistically analysed using One Way ANOVA and post-hoc LSD. Results: The result of this study showed mean and standard deviation of VHN of bioceramic sealer specimen which were soaked in white vinegar, 37% phosphoric acid, 10% hydrofluoric acid and saline as follows respectively: 45.11±2.39; 51.46±3.64; 29.77±2.66; 66.16±1.70 with p value <0.001. Conclusion: 10% hydrofluoric acid has the greatest potency as root canal solvent for bioceramic sealer during root canal retreatment.